PENGEMBANGAN PERANGKAT IoT MONITORING KUALITAS UDARA DALAM RUANGAN MENGGUNAKAN MIKROKONTROLLER BERBASIS ANDROID - Nogar Silitonga; Yuniman Telaumbanua; Harlen Gilbert Simanullang (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Air quality in a room is a problem that needs to be considered because it can affect human health. Therefore, we need a system that can monitor LPG, CO2, and cigarette smoke levels to determine the value of air quality levels in a room. Air pollution levels can be measured with the MQ-2 sensor to detect levels and an Android-based application as an information viewer. This study aims to build a monitoring application for LPG, CO2, and cigarette smoke levels based on the wireless ESP8266 sensor network in the room. The level monitoring application is built with the Java programming language, Firebase, and Arduino software. The application development stage includes analysis, system design, implementation, and testing. The level monitoring application that is made can display the results of monitoring data. So those users can find out the measurement data of a level that is in a room with a series of sensors used. The result is research on the use of this device can be used as a tool to monitor air quality in a room.